The relationship between perceived health outcomes of recreation, exercise dependence, and life satisfaction: A study with fitness center members - EMRAH SERDAR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study aimed to investigate the relationship between perceived health outcomes of recreation, exercise dependence, and life satisfaction among fitness center members. Material and methods: The study sample consisted of 490 participants, 336 males, and 154 females, who were members of a private fitness center in Istanbul. The participants were selected using a purposeful sampling method. Data collection tools included the Perceived Health Outcomes of Recreation Scale, developed by Gomez et al. and adapted to Turkish by Yerlisu Lapa et al., the Exercise Dependence-21 Scale, developed by Hausenblans and Downs and adapted by Gürbüz and Aşçı and the Life Satisfaction Scale developed by Diener et al. and adapted by Yetim. The data were analyzed using independent t-test, MANOVA, and Pearson correlation analysis. Results: The independent t-test results showed a significant difference in LSS scores by gender. MANOVA analysis results revealed that the main effect of gender on the sub-dimensions of PHORS was not significant, but there was a difference in the PSYC sub-dimension. Besides, the main effect of gender on ED-21 and all sub-dimensions was significant. Conclusions: There was a positive and moderate relationship between LSS and PHORS; a negative and low-level correlation between LSS and ED-21, and between PHORS and ED-21.